2018
DOI: 10.1177/0093650218797884
|View full text |Cite
|
Sign up to set email alerts
|

Linking News Value Theory With Online Deliberation: How News Factors and Illustration Factors in News Articles Affect the Deliberative Quality of User Discussions in SNS’ Comment Sections

Abstract: Previous research suggests that distinct characteristics of news articles, such as their news factors, account for the different participation rates in comment sections as well as the degree of interactivity among the discussants. In this study, this assumption is tested in the Facebook environment and extended to the analysis of how news factors (i.e., event characteristics) and illustration factors (i.e., characteristics resulting from a specific journalistic editing) of news articles predict the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0
11

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(59 citation statements)
references
References 57 publications
3
44
0
11
Order By: Relevance
“…We find that this same pattern holds nationally in the United States and in a data set comprised of people from 20 U.S. news sites. Second, the results add the nuance of political topics to these previous observations (Chen, 2017; Pierson, 2015) and to the Ziegele et al (in press) finding that specific types of news articles yield different commenting practices. Here, we find that not only the topic of the news article, but also the demographic attributes of the reader, influence commenting.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…We find that this same pattern holds nationally in the United States and in a data set comprised of people from 20 U.S. news sites. Second, the results add the nuance of political topics to these previous observations (Chen, 2017; Pierson, 2015) and to the Ziegele et al (in press) finding that specific types of news articles yield different commenting practices. Here, we find that not only the topic of the news article, but also the demographic attributes of the reader, influence commenting.…”
Section: Discussionsupporting
confidence: 66%
“…Ruiz et al (2011), for instance, identified two distinct communities in news comment sections across five different international news brands: those who are high in diversity and argumentation and those who are homogenous and low in argumentation. Further, newsroom policies (Ksiazek, 2015; Stroud, Scacco, Muddiman, & Curry, 2014), site architecture (Freelon, 2015; Peacock, Scacco, & Stroud, in press; Sukumaran, Vezich, McHugh, & Nass, 2011), and the qualities of news articles (Ziegele, Quiring, Esau, & Friess, in press) can affect the substance of people’s online comments.…”
Section: Women Discursive Participation and Comment Sectionsmentioning
confidence: 99%
“…Previous research found that the level of incivility in comments differs across news outlets (Ziegele, Quiring, et al, 2018). Two aspects may cause news outlets to accept or trigger deviant comments, including hostile emotions in comments: the market orientation and the position of an extreme political leaning.…”
Section: Literature Reviewmentioning
confidence: 98%
“…While social media was initially praised for providing a platform for public discourse, user comments on social media often contain high levels of negative emotions, incivility, and antipolitical rhetoric (Anderson et al, 2014; Ceron, 2015; Muddiman & Stroud, 2017; Rowe, 2015b). Particularly when political topics are discussed on social media, negative emotions seem to thrive (Trilling, 2014; Ziegele, Quiring, et al, 2018). Commenting on political news represents an engagement with journalistic content that is important to analyze, as these comments may reveal the opinions of those who are willing to engage in public debates and attempt to influence public opinion (Buckels et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation